Enhancing Discipline Through Operant Conditioning in Islamic Education at Elementary School Purnama 1 - Imami, Agus Sulthoni; Fajri, Zaenol; Rhomadona, Siti Ainun (Journal of Basic Education Research, 2025)
Purpose of the study: This study aims to identify and analyze the use of operant conditioning to improve student discipline. It is based on Islamic religious education and aims to investigate how teachers or homeroom teachers use operant conditioning in student interactions and how it affects discipline and character development. Methodology: This study employed a qualitative approach with a case study research design, which seeks to comprehend the case's dynamics and context while generating a more in-depth understanding of the phenomenon under investigation—specifically, the use of operant conditioning by teachers to students at elementary school Purnama 1. Main Findings: In this study, the form, procedure, and outcomes of using operant conditioning in schools, which is extremely important in establishing student discipline, will be revealed. When teachers or homeroom teachers consistently give rewards and punishments, children are likelier to be disciplined, which benefits the classroom learning process. Novelty/Originality of this study: The study highlights the integration of operant conditioning within the context of Islamic religious education, emphasizing the teacher's dual role as a mentor and moral role model. It explores how this approach not only influences student discipline but also contributes to the moral and behavioral development of students, potentially improving both the quality of teaching and the formation of a better generation